Favorable Response to CD34+ Cell Therapy Is Associated with a Decrease of Galectin-3 Levels in Patients with Chronic Heart Failure - Poglajen, Gregor (Dis Markers, 2019)
BACKGROUND: Galectin-3 plasma levels (gal-3) were shown to correlate with the scar burden in chronic heart failure (CHF) setting. As scar burden predicts response to stem cell therapy, we sought to explore a correlation between gal-3 and response to CD34+ cell transplantation in patients with CHF. METHODS: We performed a post hoc analysis of patients, enrolled in 2 prospective trials investigating the clinical effects of CD34+ cell therapy in patients with ischemic cardiomyopathy (ICMP) and nonischemic dilated cardiomyopathy (DCMP). CD34+ cells were mobilized by G-CSF, collected via apheresis, and injected transendocardially using NOGA system. Patients were followed for 3 months and demographic, echocardiographic, and biochemical parameters and gal-3 were analyzed at baseline and at follow-up. Response to cell therapy was defined as an LVEF increase of ≥5%. RESULTS: 61 patients were included in the analysis. The mean age of patients was 52 years and 83% were male. DCMP and ICMP were present in 69% and 31% of patients, respectively. The average serum creatinine was 86 ± 23 μmol/L, NT-proBNP 1132 (IQR 350-2279) pg/mL, and LVEF 30 ± 6%. Gal-3 at baseline and at 3 months did not differ significantly (13.4 ± 5.5 ng/mL vs. 13.1 ± 5.8 ng/mL; p = 0.72), and there were no differences in baseline gal-3 with respect to heart failure etiology (15.1 ± 7.2 ng/mL in ICMP vs. 12.7 ± 4.3 ng/mL in DCMP; p = 0.12). Comparing responders (N = 49) to nonresponders (N = 18), we found no differences in baseline gal-3 (13.6 ± 5.7 ng/mL vs. 13.2 ± 4.9 ng/mL; p = 0.80). However, responders had significantly lower gal-3 at 3-month follow-up (12.1 ± 4.0 ng/mL vs. 15.7 ± 8.4 ng/mL; p < 0.05). Also, responders demonstrated a significant decrease in gal-3 over 3 months, while in nonresponders, an increase in gal-3 occurred (−1.5 ± 5.4 ng/mL vs. +2.7 ± 4.3 ng/mL; p = 0.01). CONCLUSIONS: In patients with chronic heart failure undergoing CD34+ cell therapy, a decrease in galectin-3 plasma levels is associated with beneficial response to this treatment modality. Further prospective data is warranted to confirm our findings and to deepen our understanding of the role of gal-3 in the field of stem cell therapy.